Classification of al-Farabi’s sciences - Sandybayev, Zh.S. (Journal of Oriental Studies, 2020)
The author, explains in arabic the classification of sciences in Al-Farabi, on the basis of the treatise “Ihsaa Al-Uluum”. Useful benefits that can be achieved with the help of science is information, and the other may be used as information and practical activity at the same time. Therefore, the science of philosophy is divided into two types: “falsafatu an-nazaria” theoretical philosophy and “fәlsәfatu al-amaliya” practical philosophy. The objects of study and research of theoretical philosophy are God, space, mind, celestial bodies, natural beings, objects, flora and fauna as well as people, numbers, shapes and their dimensions, etc. The peculiarity of practical philosophy is the study of things that are still unknown than the first type of philosophy and have become the subject of study in accordance with the individual’s will and desire. Al-Farabi’s philosophy and “religious doctrine” both contain certain objects, both of which offer fundamental principles, the beginnings of matters in life, which provide knowledge about the beginnings and the first causes of matters in life, the ultimate goal of human life, namely explains how to achieve the highest happiness and the ultimate goal. The article says that al-Farabi is making an attempt to bring Muslim law and kalam closer to philosophical sciences.The author believes that fiqh and kalam are included by the medieval philosopher in a number of philosophical sciences that are based on revelation.This is also one of the new scientific methods used by al-Farabi. Key words: аl-Farabi, Arab-Muslim thinkers, Greek philosophers, science, education, art, philosophy, civil policy, physics, metaphysics, classification of sciences.